UI/UX Design for Tourism Village Website Using the User Centered Design Method - Hasna Tania Yasmine; Wahyu Tisno Atmojo (Universitas Pendidikan Nasional, 2022)
The importance of creative and innovative technology applies to any sector of industry. Technology offers a lot to improve performance in general. In the tourism sector, creative and innovative technology affects how the welfare of the community and businesses increase significantly. The use of technology can create exposure to enhance, and gain the interest of many people to the tourism itself. Developing a website or mobile based application is a way to be creative and innovative about the solution to increase the number of tourist visits. In addition to reaching the expected number of tourist visits, the application needs to be both effective and efficient in obtaining the up-to-date information regarding the destination. In this study, the User Centered Design method is used to obtain descriptive information to be used as a User Interface and User Experience design guidelines, also the User Experience Questionnaire method to assess the evaluated User Interface and User Experience outputs. One descriptive questionnaire is used as the implementation of User Centered Design, and the two User Experience Questionnaires afterward are used to assess User Interface and User Experience. The second design is appointed to be the final design of User Interface and User Experience based on the end comparison result of User Experience Questionnaire. These design methods produce a more effective output because the process involves direct evaluation from users in order to fulfill the needs and demands more precisely without overdoing the process.